Dangerous Liaisons between Beta-Amyloid and Cholinergic Neurotransmission - Govoni, Stefano; Mura, Elisa; Racchi, Marco; Lanni, Cristina; Grilli, Massimo; Zappettini, Stefania; Salamone, Alessia; Olivero, Guendalina; Pittaluga, Anna; Marchi, Mario (Current Pharmaceutical Design, 2014)
The review examines the multifaceted interactions between cholinergic transmission and beta-amyloid suggesting a continuum in the action of the peptide that at low concentrations (picomolar-low nanomolar) may directly stimulate nicotinic cholinergic receptor while desensitizing them at increasing concentrations (high nanomolar-low micromolar). In addition high beta-amyloid concentrations may reduce the synaptic release of several neurotransmitters, including glutamate, aspartate, GABA, glycine and dopamine, when the release is elicited through cholinergic stimulation but not following depolarization. The effect of beta-amyloid has been observed both in vitro and in vivo in at least three different brain areas (nucleus accumbens, striatum, hippocampus) suggesting that the peptide may exert some general effects even if not all the brain areas have been evaluated. In turn the activation of cholinergic receptors may affect the amyloid precursor protein processing diverting the metabolism toward non-amyloidogenic products. These actions, dissociated from those described in the case of high beta-amyloid concentrations leading to neurotoxic oligomers, may participate to cause dysfunctions in the neurotransmitter activity, in turn leading, at least from a theoretical point of view, to early neuropsychiatric disturbances in the disease. Complexively these observations underscore novel relationships between two main players in Alzheimer's disease pathogenesis that are beta-amyloid and cholinergic transmission. Also emerges the inherent difficulty of targeting beta-amyloid in a context in which the peptide exerts several actions beyond neurotoxicity.
Keywords: nicotinic receptors